Client characteristics and waiting time effects at a Child, Adolescent and Family Mental Health Service : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts in Psychology at Massey University - Trynes, Mariella Moana (Massey University, 1998)
The present study was of a prospective, longitudinal design which provided a 'snap-shot' overview of a Child, Adolescent, and Family Mental Health Service (CAFS). The present study had three main objectives. The first objective was to describe the characteristics of clients referred to CAFS assigned to the different priority categories. The second objective was to determine the typical waiting times for clients attending CAFS. The third objective was to determine what changes in problem symptomatology or problem severity occur whilst clients wait for their initial appointment. Two hypotheses were tested. The first was that those who are placed on the High priority wait list will have significantly higher levels of symptomatology than those on the Medium priority wait list. The second was that as wait time increases, problem severity will also increase. Participants consisted of parents/caregivers of consecutive clients who were placed on a High or Medium priority waitlist. Parents/caregivers completed the Child Behaviour Checklist (CBCL) measure when first placed on the waitlist and again before they attended their initial appointment at the service. Clients assigned to the non-wait listed categories (Crisis or Urgent) tended to consist of older females, whereas those assigned to the wait listed categories (High and Medium priority wait list) tended to consist of younger males. Results indicated that wait time did not affect problem severity, nor did problem severity differ for High and Medium priority clients. The discussion focused on the implications of the findings with regards to managing mental health waiting lists.
Keywords: New Zealand -- Palmerston North; Child mental health services; Mental health services; Youth; Mentally ill children